2015
DOI: 10.1136/oemed-2014-102547
|View full text |Cite
|
Sign up to set email alerts
|

Asthma history, job type and job changes among US nurses

Abstract: Objectives Nurses are at increased risk of occupational asthma, an observation that may be related to disinfectants exposure. Whether asthma history influences job type or job changes among nurses is unknown. We investigated this issue in a large cohort of nurses. Methods The Nurses' Health Study II is a prospective study of U.S. female nurses enrolled in 1989 (ages 24-44 years). Job status and asthma were assessed in biennial (1989-2011) and asthma-specific questionnaires (1998, 2003). Associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 40 publications
(60 reference statements)
1
34
0
1
Order By: Relevance
“…Especially, exposures to cleaning and disinfecting products may explain the increased risk of occupational asthma. 26 In our study, we observed that health-associated professionals were associated with several respiratory symptoms in the past 12 months and the use of current asthma medication. This is in line with findings from Lillienberg et al 8 showing an increased risk for new-onset asthma in female nurses (HR 1.5, 95% CI 0.95 to 2.1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Especially, exposures to cleaning and disinfecting products may explain the increased risk of occupational asthma. 26 In our study, we observed that health-associated professionals were associated with several respiratory symptoms in the past 12 months and the use of current asthma medication. This is in line with findings from Lillienberg et al 8 showing an increased risk for new-onset asthma in female nurses (HR 1.5, 95% CI 0.95 to 2.1).…”
Section: Discussionmentioning
confidence: 59%
“…These results support earlier findings from cross-sectional studies from specific industries or sectors showing that working as a healthcare professional is associated with respiratory symptoms and asthma. [24][25][26] Healthcare professionals consist of several occupational groups with a variety of potential exposures to occupational hazards that may have asthmagenic and/or allergenic properties. Especially, exposures to cleaning and disinfecting products may explain the increased risk of occupational asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The NHSII began in 1989 when 116,430 female registered nurses from 15 U.S. states, aged 25–44 years, completed a questionnaire on their medical history and lifestyle characteristics [1719]. Follow-up questionnaires have been sent every 2 years since.…”
Section: Methodsmentioning
confidence: 99%
“…These articles include case reports [84,87], as well as findings from surveillance [80,88] and epidemiologic studies conducted in general population samples [89] and among cleaning workers [90,91]. The findings from surveillance [92,93] and epidemiologic studies [34,9498] support the conclusion that asthma and related symptoms are associated with cleaning and disinfecting activities in health care facilities. For example, a study of health care workers in France reported an association of current asthma with exposure to ammonia and to sprays with moderate/high intensity, with exposure based on both expert assessment and a job exposure matrix [97].…”
Section: Case Study #3: Cleaning and Disinfecting In Health Carementioning
confidence: 95%
“…For example, a study of health care workers in France reported an association of current asthma with exposure to ammonia and to sprays with moderate/high intensity, with exposure based on both expert assessment and a job exposure matrix [97]. Participants with baseline asthma in the longitudinal Nurses’ Health Study II in the United States were more likely to change to jobs that had lower exposure to disinfectants [98]. From an investigation of health care workers in Texas, onset of asthma after entering a health care profession was associated with job exposure matrix-assessed exposure to instrument cleaning and surface cleaning products [34,95,96], and work-related asthma symptoms and work-exacerbated asthma were associated with self-reported use of various cleaning and disinfecting products [94].…”
Section: Case Study #3: Cleaning and Disinfecting In Health Carementioning
confidence: 99%